Remote Vital Signs Monitoring Based on Internet of Things System: Literature Review - Fujiasih, Asih (Universitas Padjadjaran, 2023)
Health information technology is evolving. Remote vital signs monitoring based on the Internet of Things (IoT) is an application that can improve the accessibility of health care. Vital sign measurement uses a sensor tool which data is automatically sent via IoT system, procesed and can be viewed through an application on mobile device or web. This system consists of concept, input, process, and output. This literature review aimed to find out the concept of Remote Vital Signs Monitoring Based on IoT System, input, process, and output. The methode used is through a search at Remote Lib Ui which is then selected through PRISMA methodology, so that is found 12 literature. Trough the literature review, three main concepts were obtained, namely monitoring at home, monitoring in the inpatient room, monitoring during sports. On input aspect, various sensor tools are used, three of which are integrated with the EWS/MEWS system. On the process aspect, there are microcontroller and connectivity that must be considered. . On the output aspect, three tools already have application feature designs, most of the results are displayed in the form of numbers and graphics, three of which are able to display results in the form of EWS/MEWS.. Measuring tools still need to be developed to be more integrated, simple, and accurate. Feature development and cost considerations need to be made. Subsequent studies can applied to the system in the context of an outpatient integrated with Electronic Health Record.